Longitudinal shortening of sub‐epicardial myocytes in severe ischaemic cardiomyopathy: insights from gadolinium contrast cardiac magnetic resonance imaging. (13th October 2017) - Bjerre, Jenny; Kyhl, Kasper; Gustafsson, Finn; Kelbæk, Henning; Engstrøm, Thomas; Olsen, Peter Skov; Hasbak, Philip; Vejlstrup, Niels; Madsen, Per Lav
Abstract: We present two patients with three‐vessel disease and severely depressed left ventricular (LV) systolic function where viability analysis by cardiac magnetic resonance imaging demonstrated areas of near‐transmural sub‐endocardial fibrosis and hence little chance of regaining systolic function as judged by conventional analysis from radial function. Despite the pessimistic cardiac magnetic resonance imaging analysis, however, the patients underwent full revascularization and regained impressive increases in LV systolic function mainly based on improved longitudinal systolic segment function. The cases highlight that sub‐epicardial, longitudinally oriented myocytes can contribute to overall LV systolic function and suggest taking their 'piston‐function' into consideration when analysing viability.